Influence of different wave load sequence models on fatigue life prediction of ship structures based on fracture mechanics approach - Gracia, Luis De; Osawa, Naoki; Mao, Wengang; Ichihashi, Daichi (Volume 3: Structures, Safety and Reliability, 2016)
FCP (Fatigue Crack Propagation) based fatigue assessments of a welded joint in a 2800 TEU container ship which sails on North Atlantic routes are performed. The Great-circle course with small variation of relative heading angle and a southerly course with large variation of relative heading angle are considered. Short sea sequences are generated by using ‘storm model’ developed by Osaka University and ‘spatio-temporal model’ developed by Chalmers University. Sea keeping analyses are performed for both cases wherein the variation in wave direction’s occurrence probability is considered (‘real headings model’) or not (‘all-headings model’). FCP analyses are performed considering plasticity-induced crack closure by using FASTRAN-II. Fatigue crack propagation lives and characteristics of crack propagation retardation due to excessive loads are compared. Based these results, the influence of the difference in load sequence model on FCP-based fatigue assessment result is discussed.